Diskursus Tafsir Masa Tabi’in dan Ruang Lingkupnya - Gunawan Hasibuan, Akmal Rizki; Mardian Idris Harahap; Muhammad Fakih Hasibuan; Wildan Wulandari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to analyze the interpretation of the Qur'an during the tabi'in period. This discourse is very important to study because tabi'in has an important and significant role in the field of tasfir tabiin which is the generation after the companions, because the tabiin have received interpretation from the companions directly. This research uses qualitative research with a literature study approach, The results of the study concluded that there were two models of interpretation during the tabiin period, namely the interpretation of bil-ma'tsur and bil-ro'yi while the method applied during the tabiin period was the ijmali method. So it can be concluded that the interpretation of the tabi'in era is the beginning of an interpretation involving Arab and non-Arab cultures. In addition, over time with the expansion of Islamic territory became a very important beginning of the Qur'an in the generation after Tabi'in.